Morphometry Characteristics of Riverbed Sediment Grains as Basic Indicator Management of River Valley Environment (Case Study of Bogowonto River, Central Java) - Suprapto Dibyosaputro (Forum Geografi, 2015)
This research aims to propose the usage of riverbed sediment grains roundness/flatness as basic indicator of river valley management. It is based on the evaluation of anomalous morphometry condition of sediment grains and valley condition along the river as one indicator of the stability of the riverbank of the river valley. This stability express the physical condition of the river valleys. In this paper, we provide methodological explanation as well as a case study in Bogowonto River. Analysis of the morphometry of sediment grain on riverbed from upstream to downstream as well as the relationship between the distance of the upstream and morphometry of sediment grains along Bogowonto River were conducted. Finally, we evaluated the anomalous condition as indicator of different environmental condition of the riverbank. We conducted three stages survey processes: preparation, fieldwork, and post-fieldwork. The preparation phase includes site selection, depiction of the main river channel of Bogowonto River, and the determination of the sample location. The distance between each sampling site was 5 km along Bogowonto River. The results show that there is anomalous morphometry of sediment grains found in the study area. The reason is that the channel of the segment of the river flowing over rocky riverbed of breccia along the 7.5 km, with hard and sharps edge grained of rock particles. This is accompanied by landslide the occurrence in the upper segment of the river. This is why the value of roundness and flatness indexes are changed significantly become lower value than the previous segment. This condition can be implemented to be used as indicator to basic management of landslide along a certain segment which indicated by the changing in roundness and flatness index values of the sediment grains.